Case Against a Copper Tariff - AIME AIME (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
THAT the copper industry is in serious straits is admitted. So are the lead and zinc industries, and both lead and zinc are tariff protected. Conditions in the Western lead, zinc and silver mining districts are desperate. These are illustrated by the present disastrously low prices of these metals compared with the levels of two and three years ago and by the comparative rates of metal production and the present activity of the western mining camps. The January production of copper was 32.2 per cent of the 1929 average rate, of steel was 32.3 per cent of the 1929 average, while January production of pig iron was only 27.6 per cent of the monthly average of 1929. The copper industry is only one of many industries that are suffering in this tragic depression. It has been exceedingly prosperous and will be prosperous again when business recovers. Its difficulties are not unique and it does not deserve the tariff equivalent of a dole. The burden of subsidizing through an effective tax or tariff the minority group of high-cost mines would be a heavy one on the consuming public of the United States. On the basis of 1929 consumption figures, an effective 5c. tariff would result in an increased copper bill to the country of over $109,000,000, of which the electric manufacturers would contribute $26,000,000, the telephone and telegraph companies $16,000,000, and the automobile manufacturers $14,000,000. And of this total bill, only $33,000,000 would go to those who are urging a tariff and the balance of $76,000,000 would be paid to those who do not admit either its necessity or usefulness under present conditions.